Anna Maria's gift - Shefelman, Janice Jordan, 1930- (Random House Children's Books, 2010)
In 1715 Italy, eight-year-old Anna Maria Lombardini arrives at a Venice orphanage with little but the special violin her father made for her, but when her teacher, Antonio Vivaldi, favors her over a fellow student, the beloved instrument winds up in a canal. Includes glossary and historical note.